T2∗ Relaxation Time Obtained from Magnetic Resonance Imaging of the Liver Is a Useful Parameter for Use in the Construction of a Murine Model of Iron Overload. (22nd September 2019) - Matsuo-Tezuka, Yukari; Sasaki, Yusuke; Iwai, Toshiki; Kurasawa, Mitsue; Yorozu, Keigo; Tashiro, Yoshihito; Hirata, Michinori
Abstract : Aim . Iron overload is a life-threatening disorder that can increase the risks of cancer, cardiovascular disease, and liver cirrhosis. There is also a risk of iron overload in patients with chronic kidney disease. In patients with renal failure, iron storage is increased due to inadequate iron utilization associated with decreased erythropoiesis and also to the inflammatory status. To evade the risk of iron overload, an accurate and versatile indicator of body iron storage in patients with iron overload is needed. In this study, we aimed to find useful iron-related parameters that could accurately reflect body iron storage in mice in order to construct a murine model of iron overload. Methods . To select an appropriate indicator of body iron status, a variety of parameters involved in iron metabolism were evaluated. Noninvasively measured parameters were R1, R2, andR 2 ∗ derived from magnetic resonance imaging (MRI). Invasively measured parameters included serum hepcidin levels, serum ferritin levels, and liver iron contents. Histopathological analysis was also conducted. Results/Conclusion . Among the several parameters evaluated, the MRIT 2 ∗ relaxation time was able to detect iron storage in the liver as sensitively as serum ferritin levels. Moreover, it is expected that using an MRI parameter will allow accurate evaluation of body iron storage in mice over time.